2020
DOI: 10.1515/secm-2020-0045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cooling Rate and Austenite Deformation on Hardness and Microstructure of 960MPa High Strength Steel

Abstract: In order to develop 960MPa grade high strength steel, the effects of cooling rate and austenite deformation on the hardness and the microstructure of high strength steel has been studied by Scanning Electron microscope (SEM), Transmission Electron Microscope (TEM), Gleeble-3500 thermal simulation testing machine and T2500 Vickers hardness tester. The results show that only when the cooling rate was higher than 10∘C/s and the final cooling temperature was lower than 250∘C, the microstructure mainly consists of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…The size of the martensite lath was gradually refined with an increase in cooling rate of 10-40 C/s so that many entangled dislocations were distributed within the martensite lath boundary [21]. Rapid cooling rates (aqueous medium or exceeding 10 C/s) tend to produce martensite lath, while fairly fast cooling rates (oil media) allow the transformation of lower bainite or martensite to larger/coarse sizes.…”
Section: Microstructure and Hardness Analysismentioning
confidence: 99%
“…The size of the martensite lath was gradually refined with an increase in cooling rate of 10-40 C/s so that many entangled dislocations were distributed within the martensite lath boundary [21]. Rapid cooling rates (aqueous medium or exceeding 10 C/s) tend to produce martensite lath, while fairly fast cooling rates (oil media) allow the transformation of lower bainite or martensite to larger/coarse sizes.…”
Section: Microstructure and Hardness Analysismentioning
confidence: 99%
“…The metastable phase depends on the nonequilibrium cooling, the chemical composition, and section size of the forging [13]. Martensite lath has gradually been refined with the cooling rate increase [14]. In the moderate cooling rate (oil quenchant), Fig 3(c,d) comprise of acicular bainite and ferrite.…”
Section: Ramentioning
confidence: 99%
“…Mo can decrease the ferrite transformation temperature but increase the diffusion activation energy of carbon in austenite and reduce the diffusion coefficient of carbon. It can also effectively promote the formation of acicular ferrite [14].…”
Section: Ramentioning
confidence: 99%
“…M s of 960 MPa grade high strength steel is about 443 °C, the critical cooling rate of martensitic transformation is about 10 °C/s, and M f is about 259 °C. Moreover, when the cooling rate is not above 3 °C/s, the austenite transformation product would be bainite and martensite, which would affect the strength of high strength steel, Table 1, Figure 1 [14].…”
Section: Numerical Simulation and Experimental Program 21 Direct Quen...mentioning
confidence: 99%
“…Studies have shown that for 960 MPa high strength steel, martensite begins to appear when the cooling rate > 3 °C/s, and full martensite can be obtained when the cooling rate � 10 °C/s [14,15]. When the final cooling temperature is below 300 °C, the strength of high strength steel can meet the requirements of � 960 MPa [16].…”
Section: Introductionmentioning
confidence: 99%